1982
DOI: 10.3758/bf03197637
|View full text |Cite
|
Sign up to set email alerts
|

Why do categorization effects occur in comparative judgment tasks?

Abstract: Three experiments were conducted to understand what eliminates the symbolic distance effect for reaction times (RTs) when subjects learn that items belong to categories. Artificial city locations were judged, and artificial states served as categories. In Experiment I, whether or not categories were presented and the amount of categorization practice were manipulated. Only those subjects who had practice categorizing cities into states showed a reduced symbolic distance effect for different-state pairs. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 13 publications
3
20
0
Order By: Relevance
“…In essence, social bonds functioned to mitigate the distancing effect of spatial boundaries by bringing two locations closer together, psychologically speaking. This finding fits with the results of existing work on judgments for between-and within-boundary estimations (Hirtle & Jonides, 1985;Maki, 1982;McNamara, 1986;.…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…In essence, social bonds functioned to mitigate the distancing effect of spatial boundaries by bringing two locations closer together, psychologically speaking. This finding fits with the results of existing work on judgments for between-and within-boundary estimations (Hirtle & Jonides, 1985;Maki, 1982;McNamara, 1986;.…”
Section: Methodssupporting
confidence: 82%
“…For example, Stevens and Coupe (1978) demonstrated that perceptual boundaries (e.g., state borders) promoted use of categorical knowledge; judgments about the relative location of cities relied on knowledge about the relative locations of the states containing the cities. Locations that share membership in a superordinate region are perceived to be more similar to one another and more distinct from locations not sharing such membership, regardless of their own specific characteristics (Hirtle & Jonides, 1985;Maki, 1982;McNamara, 1986;. These findings suggest that spatial-learning goals and an environment's spatial and perceptual features impact the content and structure of spatial mental representations.…”
Section: Structuring Spatial Informationmentioning
confidence: 64%
See 1 more Smart Citation
“…Studies examining category effects on spatial memory have generally used Euclidean (straight-line) distance estimation or relative direction judgments (Maki, 1982;Hirtle & Jonides, 1985;Hirtle & Mascolo, 1986;Hirtle & Kallman, 1988;McNamara & LeSueur, 1989;McNamara et al, 1992;Hommel et al, 2000;Friedman & Montello, 2006). Such tasks emphasize the global (e.g., bird's-eye) relation between locations in that they can be accomplished efficiently by retrieving an allocentric overview of an environment.…”
Section: Global Vs Local Spatial Information Processingmentioning
confidence: 99%
“…(c) Categorical knowledge and categorical inference-Complex realworld knowledge is often categorical in nature, and there is ample evidence that categorical information plays an important role in both estimation and paired-comparison tasks (e.g., Brown & Siegler, 1991;A. Friedman & Brown, 2000a, 2000bMaki, 1981Maki, , 1982Sailor & Shoben, 1996). Categorical knowledge seems to be particularly relevant in judgments about attributes of countries (W. J.…”
Section: The Mac Frameworkmentioning
confidence: 99%